NEURO-PSYCHOLOGICAL APPROACH TO TEACHING GENERAL ENGLISH TO THE FIRST YEAR STUDENTS OF THE TRANSLATION DEPARTMENT - Vysotskaya, Tatyana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The work deals with the problems of improving General English teaching materials for undergraduates in terms of the neuro-psychological trends in Foreign Language Teaching Methodology and developing a tutorial based on the knowledge of students’ cognitive styles caused by the individual profile of the functional asymmetry of the brain, i.e. we aim at proposing the methods of neuropsychological approach implementation in the educational process. The topicality of the research is attributed to the lack of teaching materials applying neuro-psychological approach, though it is proved to be productive, as its implementation is known to help the process of mastering a foreign language. The primary methods used are as follows: observation, pedagogical experiment, statistical processing of data. Neuro-psychologically grounded teaching methodology forms the basis of the English language successful mastering, as it takes into account such extremely important features of the student as the profile of his inter-hemispheric asymmetry, which in its turn determines the specific cognitive style, and hence the type of mastering the foreign language.